Collaborative Weblog-Based (CWB) Project Approach in Developing Language Learners’ Writing Performance - Rivera, Maricel; Bacus, Remedios (International Journal of Learning, Teaching and Educational Research, 2023)
Advancements in educational technology have kept teaching and learning undisrupted during unprecedented times. Individual and collaborative web-based learning activities have addressed language teachers’ dilemma on how to approach teaching and learning remotely. Weblogging characterised by online journals has been considered to address students’ difficulty in mastering writing as a productive skill. In this study, the effectiveness of a collaborative weblog-based (CWB) project approach was explored. Utilising a quasi-experimental design, 56 English pre-service teachers enrolled in a state university were purposively selected to be the study participants. The validated pre-post-test questionnaire, course syllabus, lesson exemplars, and scoring rubric were used to gather the needed data on students’ writing skills. Results of the paired t-test revealed a significant increase in the three aspects: organisation, elaboration and grammar, usage and mechanics. The CWB project approach is an alternative way to improve students’ writing performance. It is recommended that CWB project may be used by teachers handling writing courses and other related disciplines to address writing proficiency. https://doi.org/10.26803/ijlter.22.3.11